Empirical Analysis of the Borrowing Behavior of Indian Firms on the Backdrop of the Pecking Order Model - Chakrabarty, Anindya (Indian Journal of Finance, 2011)
The paper explores various facets of the pecking order theory over 147 BSE listed A-Group companies for a period of ten years (2000-2009) and obtained a mixed result. When, on the one hand, it supports Halov and Heider’s finding that pecking order is a special case, which works best when the external investors do not care about not knowing the risk of the project, on the other hand, it questions the aggregation model used by Shyam-Sunder and Myers and others in defining the financial deficit for testing the theory. It is depicted empirically that at times of higher dividend payout, the change in borrowing level decreases, which advocates the separation of dividend payout from the aggregated "financial deficit" used in the regression studies. Along the same line, it is also observed that the degenerated form of the pecking order model works best among the Indian firms, as compared to the original aggregation model. The paper further reveals a non-linear (U-shape) relationship between the change in the borrowings and the change in the retained earning position of the firms, which accounts for the inclination of the firms toward higher debt at times of high profitability.